2006
DOI: 10.1167/iovs.05-0988
|View full text |Cite
|
Sign up to set email alerts
|

Otago Glaucoma Surgery Outcome Study: Cytology and Immunohistochemical Staining of Bleb Capsules around Molteno Implants

Abstract: The balance between activation and apoptosis regulates the thickness and permeability of bleb capsules, and the normal lifecycle of bleb capsules includes continual inner surface degeneration and external surface renewal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…The available literature is scant and the few concerned studies have investigated histological changes in encapsulation related valve failure. Most of the studies are based on small sample sets (eg, n = 1, 3, 5, 6, 9, 10) and also not always uniform for the implants used [1113,2730]. Nevertheless, these studies have provided valuable histopathological insight.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature is scant and the few concerned studies have investigated histological changes in encapsulation related valve failure. Most of the studies are based on small sample sets (eg, n = 1, 3, 5, 6, 9, 10) and also not always uniform for the implants used [1113,2730]. Nevertheless, these studies have provided valuable histopathological insight.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we investigated those factors associated with fibroblast activities, and observed FBGCs in detail. Molteno et al 24,25 investigated histologic features of capsules between 4 days and 23 years after insertion of Molteno implants in human. They showed that the capsule was thicker with immediate drainage of aqueous (one-stage technique) compared with delayed drainage of aqueous (the second stage of a two-stage insertion).…”
Section: Discussionmentioning
confidence: 99%
“…Use of Baerveldt GDDs in human glaucoma patients has been associated with lower adjunctive medications and rates of additional surgery compared to Ahmed devices. 11,[21][22][23][24] The relatively larger size of the scleral endplate has been shown clinically and experimentally in humans to correlate with better drainage capacity compared to smaller devices. 12,13,25 Investigations into the pathogenesis of implant failure in humans have focused on managing the postoperative inflammatory response, minimizing the risk and duration of hypotony, as well as managing the fibroproliferative response to help maintain a functional 'draining bleb' around the implant.…”
Section: Introductionmentioning
confidence: 99%
“…12,13,25 Investigations into the pathogenesis of implant failure in humans have focused on managing the postoperative inflammatory response, minimizing the risk and duration of hypotony, as well as managing the fibroproliferative response to help maintain a functional 'draining bleb' around the implant. 22 Pro-inflammatory factors present in glaucomatous aqueous accelerate fibrosis associated with the scleral endplate. 22 Therefore, in addition to controlling postoperative inflammation with anti-inflammatory medication, recommendations to minimize exposure of the developing bleb to glaucomatous aqueous by delaying aqueous flow through the shunt have been proposed.…”
Section: Introductionmentioning
confidence: 99%